MockAI : Smart Recruitment Counseling using Artificial Intelligence - Wagh, S.K; Agarwal, DO; Hire, L.S; Choudhary, JN (International Journal of Computer Sciences and Engineering, 2019)
Preparing for job interviews is very difficult. A lot of candidates are not prepared for the interviews and so they are not able to fetch their dream jobs. Mostly candidate's selection is based on the answers given in the interview. People will definitely hire those candidates who show interest and positive attitude. Using deep learning techniques we are proposing an application framework which would help candidates in preparing for the interviews. This involves multiple neural networks working separately for predicting different sections of an interview and providing real-time feedback and a report. Using CNN emotional analysis is performed on the video stream and Recurrent neural networks are utilized for sentiment analysis. Further, this Recurrent neural network with LSTM units is utilized for chat-bot interaction during the process. The chat-bot ask the questions to the candidate and candidate's response is recorded and analysis is done. All these analyses together will try to prepare the candidate for the interview as a whole